Lessons learned from radiation dose index monitoring system implementations: Challenges and outcomes. (September 2016) - Lafay, Camille; Thery, Donat; Zanca, Federica
Abstract : Introduction: Many facilities have implemented a radiation dose index monitoring (RDIM) system, due to increasing public concern over the use of ionizing radiation, to comply with national and European regulations or for accreditation purposes. Purpose: To present the challenges and the outcomes associated with the implementation of an RDIM system across several European facilities. Methods and materials: Trough the installation of a dose-monitoring software (DoseWatch, GE Healthcare) in 21 European facilities, processes and dose data were collected from CT, Mammography, RF and CV/IR systems, to evaluate challenges and outcomes. The application of a Dose Excellence Program, based on the Justification of high doses, on the Standardization of protocols in terms of RADLEX mapping and on the optimization of protocols was evaluated, to determine measurable outcomes. Results: For all sites major challenges were the "labelisation" of the procedures and the automated reporting for performance indicators tracking. Examples of outcomes are: an increased number of standardized numbers of series per protocol (up to >90% for some sites), as well as a high number of justified alerts (up to 100% in several sites). Of all justified CT alerts, the most reported reason was patient overweight or extra series needed, for CV/IR it was the difficulty of the procedure and for RF it was the use of fluoroscopy for positioning. Conclusion: The deployment of a Dose Excellence Program along with a standardized JSO report allowed all sites to move from dose tracking to dose management, trough increased awareness and sustainability of the project.